Causal relationship between gastroesophageal reflux disease and chronic obstructive respiratory disease: A bidirectional Mendelian randomization study - Shan Lin; Dingfeng Lai; Wanmei He; Qingyuan Zhan (Heliyon)
Background: Numerous observational studies have posited that gastroesophageal reflux disease (GERD) might amplify the risk of chronic airway conditions such as chronic obstructive pulmonary disease (COPD) and asthma. Yet, a definitive causal link remains to be established. To this end, we utilized a two-sample Mendelian randomization approach (MR) to investigate the potential causal dynamics between GERD and these chronic obstructive respiratory diseases. Methods: Using a two-sample bidirectional MR, we explored the causal influence of GERD on the risks of developing COPD and asthma, drawing on aggregated genome-wide association study data from European cohorts. Results: Our analysis elucidated a notable causal relationship, with individuals genetically inclined towards GERD exhibiting a significantly elevated propensity to develop COPD (odds ratio [OR] = 1.520, 95 % confidence interval [CI] 1.376−1.680, P = 2.173 × 10−16) and asthma (OR = 1.420, 95 % CI 1.340−1.504, P = 1.269 × 10−32). The absence of heterogeneity and pleiotropy was confirmed through the Cochran Q test, funnel plots, MR-Egger intercept test, and MR-PRESSO. Directional causality was further substantiated by Steiger testing. Conversely, reverse MR analyses did not identify a significant causal pathway between COPD or asthma and GERD onset. Conclusion: This investigation substantiates a robust positive correlation between GERD and increased risks for COPD and asthma, laying a foundational basis for incorporating GERD management into preventive and therapeutic strategies for these chronic obstructive respiratory diseases.